A Genre Analysis of Masters and Doctoral Dissertation Introductions in the Sciences and Social Sciences - Arulandu, Mosharakini (2006)
Introductory chapters are an integral part of dissertations. However, many postgraduates find it difficult to write them because they only implicitly understand and unconsciously follow the rules, conventions and norms placed by their respective disciplines and institutions. Therefore, comprehension of how to frame and structure the introduction is vital and is made possible by studying the generic structure of Dissertation Introductions (DIs) from various disciplines.